Emergence of endemic MLST non-typeable vancomycin-resistant Enterococcus faecium. (15th August 2016) - Carter, Glen P.; Buultjens, Andrew H.; Ballard, Susan A.; Baines, Sarah L.; Tomita, Takehiro; Strachan, Janet; Johnson, Paul D. R.; Ferguson, John K.; Seemann, Torsten; Stinear, Timothy P.; Howden, Benjamin P.
Abstract : The authors used whole-genome sequencing to identify 65 MLST non-typeable isolates of Enterococcus faecium that were resistant to vancomycin and appeared to be causing an outbreak across Australia. Abstract : Background: Enterococcus faecium is a major nosocomial pathogen causing significant morbidity and mortality worldwide. Assessment of E. faecium using MLST to understand the spread of this organism is an important component of hospital infection control measures. Recent studies, however, suggest that MLST might be inadequate for E. faecium surveillance. Objectives: To use WGS to characterize recently identified vancomycin-resistant E. faecium (VREfm) isolates non-typeable by MLST that appear to be causing a multi-jurisdictional outbreak in Australia. Methods: Illumina NextSeq and Pacific Biosciences SMRT sequencing platforms were used to determine the genome sequences of 66 non-typeable E. faecium (NTEfm) isolates. Phylogenetic and bioinformatics analyses were subsequently performed using a number of in silico tools. Results: Sixty-six E. faecium isolates were identified by WGS from multiple health jurisdictions in Australia that could not be typed by MLST due to a missing pstS allele. SMRT sequencing and complete genome assembly revealed a large chromosomal rearrangement in representative strain DMG1500801, which likely facilitated the deletion of the pstS region. Phylogenomic analysis of this population suggests that deletion of pstS within E. faecium has arisen independently on at least three occasions. Importantly, the majority of these isolates displayed a vancomycin-resistant genotype. Conclusions: We have identified NTEfm isolates that appear to be causing a multi-jurisdictional outbreak in Australia. Identification of these isolates has important implications for MLST-based typing activities designed to monitor the spread of VREfm and provides further evidence supporting the use of WGS for hospital surveillance of E. faecium .